GROUP WORK IN ENGLISH LANGUAGE CLASSES AS A MEANS OF DEVELOPING STUDENTS' COMMUNICATIVE COMPETENCE - Konovalova, V.V. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article presents the experience of using group work in professional English classes. The author presents developed tasks for organizing group work. The article also describes the advantages and disadvantages identified during the work.
Keywords: group work; individual work; frontal work; study session; professional English